2014
DOI: 10.19173/irrodl.v15i4.1840
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the effect of learning styles and study habits of distance learners on learning performances: A case of an introductory programming course

Abstract: This study examined the relationships among learning styles, study habits, and learning performances in an online programming language course. Sixty-two sophomore students who enrolled in an online introductory programming course participated in the study. Kolb's Learning Style Inventory (LSI) was used to measure the students' learning styles. Another inventory developed by the researcher was used to determine learners' study habits. An achievement test was used to put forward their learning performances.As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 34 publications
1
30
0
3
Order By: Relevance
“…This means that there is a strong relationship between the learning style and study habit of BSN students in Al Jabal Al Gharbi University in Gharyan, Libya. The finding is similar to a study conducted [47] that significant relationships between learning styles, study habits, and learning performances were revealed. Another study that coincide with our finding [48] that the result showed learning styles were found to be significantly correlated to study habits at which learning style is important predictors of a study habit.…”
Section: Discussionsupporting
confidence: 90%
“…This means that there is a strong relationship between the learning style and study habit of BSN students in Al Jabal Al Gharbi University in Gharyan, Libya. The finding is similar to a study conducted [47] that significant relationships between learning styles, study habits, and learning performances were revealed. Another study that coincide with our finding [48] that the result showed learning styles were found to be significantly correlated to study habits at which learning style is important predictors of a study habit.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, adaptive learning has been interchangeably used by Yang, Hwang and Yang (2013) in their study that focused on the development of adaptive learning by considering students' preferences (Dwivedi and Bharadwaj, 2013) and characteristics, including learning styles (Çakıroğlu, 2014;Klašnja-Milićević, Vesin, Ivanović and Budimac, 2011) and cognitive styles (Lo, Chan and Yeh, 2012) which concluded to be effective. Wang and Liao (2011) defined adaptive learning as a developed system (Lu, Chang, Kinshuk, Huang and Chen, 2014) to accommodate a variety of individual differences (Scheiter et al, 2019;Wang & Liao, 2011) such as gender, learning motivation, cognitive type, and learning style to determine optimal adaptive learning experience that accommodates a variety of individual differences (Afini Normadhi et al, 2019) to remove barriers of time and location.…”
Section: Adaptive Learningmentioning
confidence: 99%
“…Although Facebook groups have been identified as being useful in faculty-rooted course support, as well as representing organic (self-organizing) student-based learning environments [ 16 ], and although these groups combine many of the aforementioned attributes essential for educational usage, very little is known about which students use these groups, how and for what exact purpose [ 17 ]. Some researches argue that certain learning styles are more beneficial for learning through SNSs, but further research is necessary to examine these findings in different settings [ 18 - 22 ].…”
Section: Introductionmentioning
confidence: 99%